STUDY OF BACTERICIDAL ACTIVITY OF DIFFERENT SOAPS AGAINST SALMONELLA TYPHI - Farzana, Kalsoom; Batool, Shazia; Jabeen, Farzana; Shah, Syed Nisar Hussain (Journal of Research (Science), 2004)
A prospective bactericidal activity of various market soaps were performed against Gram-negative bacteria, i.e. Salmonella typhi. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by the NCCLS reference microdilution technique. The minimum inhibitory concentrations (MICs) of Johnson and Johnson baby soap and Dettol soap were 1024 μg ml-1 and 2048 μg ml-1 respectively. Whereas, the MIC value was 3072 μg ml-1 for Safeguard. Phenol and Sufi soap had similar activity against S. typhi with MIC of 6144 μg ml-1. Lux and Lifebuoy white had higher inhibitory activity against Salmonella typhi with MIC of 12288 μg ml-1, whereas Lifebuoy red had 8192 μg ml-1. The bactericidal activity of these soaps was in decreasing order as Sunlite, Lifebuoy white, Lux, Lifebuoy red, Sufi soap, Phenol, Safeguard, Dettol and Johnson and Johnson baby soap respectively. Moreover, the minimum inhibitory concentration of all soaps does not vary significantly against S. typhi. However, the minimum bactericidal concentration was significantly different among all the market soaps.